Effect of Partitioning Heattreatment Temperature on Damping Properties of ADI - LIU Xiao-Yu; WANG Li-ping; GUO Er-jun; FENG Yi-cheng; YI Peng-yue (Journal of Harbin University of Science and Technology)
In view of the traditional heat treatment process of austempered ductile iron( ADI) ，the damping performance，there is still a gap to the standard of high damping alloy． Take the two-step method of quenchingpartitioning heat treatment process，the damping properties of different partitioning heattreatment temperatures’ADI were studied systematically，The experimental results showed that: Fixed partition temperature is 360 ℃，whenthe strain amplitude is lower，whenthe quenching temperature is 240℃，ADI has the best damping properties; When the strain amplitude is higher，whenthe quenching temperature is 260℃，ADIhas the best damping properties; internal friction valuesQ －1 ＞0． 01，reach the standard of the high damping alloy． when the quenching temperature is 280℃， ADIhasthe has the lowest storage modulus． Fixed partition temperature is 360℃，whenthe partitioning temperature is 320℃，ADI has the best damping properties． The highest internal friction values Q －1 reached to 0． 017; When thepartitioning temperature is 360℃，ADI has the lowest storage modulus．